Carbon Footprint of Railway Projects Under the Belt and Road Initiative and the Future Low‐Carbon Pathways - Xin Wang; Jing Meng; Miaomiao Liu; Jun Bi (Earth's Future, 2023)
Abstract The Belt and Road Initiative (BRI) makes headway in constructing railway projects invested by China, yet related environmental impacts are rarely discussed. Here we quantify the carbon footprint of railway project construction (RPC) under the BRI and identify the drivers behind their variations to find possible carbon reduction pathways. Our results show that China‐invested overseas RPC in BRI countries induced 2,095.2 Mt CO2 emissions through the global supply chains during 2008–2017. Specifically, 73% of the carbon footprint relies on supply chains in BRI countries, and 27% spills over to other regions serving as the suppliers of global resources. Upgrading key industries' technological levels in BRI countries to China's average level can mitigate the carbon footprint by 77%. Once all industries achieve China's average technological level, nearly 90% of the carbon footprint can be avoided. The findings potentially provide valuable insights into achieving sustainable project construction in cross‐regional cooperation and promoting green development of the BRI.